ANALISIS KOMPARATIF DESAIN KEMASAN PRODUK SABUN BATANG JENAMA FRAGRANDE PASAR DOMESTIK DAN EKSPOR BERDASARKAN ELEMEN VISUAL PADA TEORI DESAIN KEMASAN - Sugilar, Audya Pridita; Soegoto, Eddy Soeryanto; Wahdiniwaty, Rahma; Sumitra, Irfan Dwiguna; Bachtiar, Adam Mukharil (Universitas Komputer Indonesia, 2025)
Fragrande is an Indonesian local brand offering beauty care products consisting of body care and fragrance items. The brand plans to expand into international markets by introducing several products, including bar soap, body mist, nourishing hair oil, perfume oil, and face mist. Differences in target markets cause a product to adopt different packaging designs between domestic and export distribution. These changes involve visual design elements that shape the product’s character. This study aims to analyze the differences in visual elements of the packaging of Fragrande bar soap for domestic and export markets based on the visual elements in the packaging design theory of Klimchuk and Krasovec. The research employs a descriptive qualitative comparative method through visual observation of Fragrande bar soap packaging. The analysis is conducted by identifying packaging visual elements, including color, typography, layout, space, and material, and examining them through the design principles of balance, hierarchy, contrast, unity, and simplicity. The urgency of this research lies in contributing academically to visual communication design studies in product packaging, providing a reference for designers in developing packaging for global markets, and demonstrating that design changes are not merely aesthetic but function as a visual positioning strategy. The results show that the domestic packaging tends to present a dense and informative visual structure, whereas the export packaging displays a simpler composition emphasizing an emotional experience approach through hierarchy. Key Words: packaging, branding, local products, export products, design communication visual